2019
DOI: 10.1177/1941738119846502
|View full text |Cite
|
Sign up to set email alerts
|

When Is It Safe to Return to Sport After ACL Reconstruction? Reviewing the Criteria

Abstract: Context: There is an ever-increasing trend toward sports, fitness, and recreation activities, so the incidence of anterior cruciate ligament sports injuries has increased. Perhaps the greatest challenge for sports clinicians is to return the injured athlete back to his/her original sport at an even greater level of functional ability than preinjury. For this, rigorous and well-researched criteria are needed. Evidence Acquisition: Using medical subject headings and free-text words, an electronic search was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 48 publications
1
69
0
2
Order By: Relevance
“…Since then, the issue of RTS criteria has received much attention in light of the unacceptable failure rates in young athletes cited by multiple investigations. 7,19,41,47,58,84,91,98,101 In 2016, Ardern et al 5 presented consensus statements regarding recommendations for RTS decision making from the First World Congress in Sports Physical Therapy. These authors identified the need to validate clinical tests for RTS, which include strength (rate of force development, eccentric, and endurance), neuromuscular control (dynamic functional tests and reactive agility tasks), psychological measures, and performance and skill execution.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the issue of RTS criteria has received much attention in light of the unacceptable failure rates in young athletes cited by multiple investigations. 7,19,41,47,58,84,91,98,101 In 2016, Ardern et al 5 presented consensus statements regarding recommendations for RTS decision making from the First World Congress in Sports Physical Therapy. These authors identified the need to validate clinical tests for RTS, which include strength (rate of force development, eccentric, and endurance), neuromuscular control (dynamic functional tests and reactive agility tasks), psychological measures, and performance and skill execution.…”
Section: Discussionmentioning
confidence: 99%
“…125 Thus, physical/physiological performance factors, which based on the present review include RFD, may explain the better rate of return to sport of elite athletes compared to recreational athletes. While modifiable neuromuscular factors such as quadriceps strength seem to have a supporting 35 and weak association 26,126 with a successful RTS after ACLR, the present data suggest the relevance of RFD testing to identify trainable neuromuscular deficits in preparation for RTS and may be especially important for athletes who are required to perform rapid/high-force movements in training and competition.…”
Section: Modifiable Neuromuscular and Physiological Risk Factorsmentioning
confidence: 56%
“…In summary, I think it is clear to most clinicians in sports medicine that our progress in understanding the full implications of an ACL injury and the complexities of returning to sport has been painfully and frustratingly slow. However, as the science of the 4 publications [7][8][9]15 in this issue of Sports Health demonstrates, we are making progress. Hopefully soon, additional strong medical research will drive our treatments in the right direction; this will improve ACL injury and reinjury rates.…”
mentioning
confidence: 99%
“…For those clinicians struggling with RTP issues, the review by Kaplan and Witvrouw 8 emphasizes 5 criteria to consider during the process. While strength, performance, and functional testing are used most commonly to determine safe RTP, the authors question the scientific validity of these factors, emphasizing the sobering fact that those who return to pivot and contact sports have a 4.68 times higher rate of knee reinjury than those who do not return to sporting activity.…”
mentioning
confidence: 99%